Operational assessment of speed control measures on capacity of urban roads in metropolitan area of Barranquilla, Colombia (2023)
With the aim to reduce accident rates and assist in pedestrian traffic, in the city of Barranquilla (Colombia), electronic devices for speed control (speed cameras) have been installed on roads of high vehicular flow with difficulty in pedestrian transit. Traffic Calming Measures are described in the literature as a set of measures to regulate traffic on roads, ensure mobility, and reduce accidents. This article focuses its study on the impact of Traffic Calming Measures through electronic devices on urban or inner cities roads (capacity and operating speed on them). This study centers in the evaluation of the operational impact of speed cameras and the data of vehicular speed and flow collected through them in four main roads of the city, with the purpose of estimating models that establish relationships of speed-flow, and analyzing the impact of these Traffic Calming Measures on the vehicular capacity of urban roads. In the estimation of road capacity, a Greenshields model was applied, with which via speed–density and flow-density relationships, we aim to determine how operational transit is affected by the use of speed cameras. Conclusions show that operational transit is affected by diminishing road capacity between 7 to 41 percent and these Traffic Calming measures are ineffective to ease pedestrian traffic as is expected.